Hubungan Antara Minta Baca dan Motivasi Terhadap Hasil Belajar Pendidikan Agama Islam Siswa Kelas V SD - Juwita, Ira; Fadillah; Nasution, Fania Aftisya (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2023)
The purpose of this study: (1) Knowing the relationship between reading interest and learning outcomes (2) Knowledge about the relationship between learning motivation and language learning outcomes (3) Knowledge about the relationship between reading interest and learning motivation and learning outcomes in Islamic Religious Education This type of research is retrospective and is correlative. Retrospective research is research that looks for relationships that are not manipulated by the researcher. The population of this study consisted of students from an elementary school in the city of Makassar with 100 students. data collection technology with a questionnaire. The research tool used was a Reading Interest Questionnaire and Learning Motivation Questionnaire with a Likert Rating Scale, alternative answers consisted of four choices, namely: I fully agree (SS; agree (S); disagree (TS); Strongly Disagree (STS). Data analysis techniques consist of descriptive analysis and inferential analysis showing search results (1) There is a significant relationship between interest in reading and studying Islamic Religious Education (2) There is a relationship between learning motivation and Indonesian learning outcomes (3) There is a significant relationship between reading and read Motivation to learn about Islamic Religious Education learning outcomes.